El derecho constitucional de la libertad y su influencia en la interposicion del habeas corpus - Peñafiel Villarreal, Irina Micaela (2013)
The present thesis with the topic concerning the Constitutional Law of Freedom and its influence on the filing of habeas corpus was made after analyzing the different texts and laws that regulate their study . To carry out the research , we conducted an a nalysis of the problem described , its causes and influences , which showed the completion of the subject, The objectives that I point out in the doctoral thesis have been met in full, of which proceeded to develop the proposed amendment to Article 44 paragraph 3 of the Law on Constitutional and Constitutional Control in Habeas Corpus analysis to guarantee the right to freedom , it was determined that world advanced level in realizing this committing right to freedom as a human right which should not be undermined by any authority . The variables and hypotheses were raised and the same once the fieldwork were tested , the positivism of the questions posed to citizens led to the testing of the hypothesis which is accepted. The field research through surveys conducted to guide citizens of Quevedo Canton , the same that developed normally asking questions easily accessible to citizens surveyed in order to obtain answers that define the knowledge of Habeas Corpus , the applicability and influences the methods used and applied research in the field were used to determine and design research. In the theoretical background of the research is carried out a synthesis of the origins of Habeas Corpus, doctrine identifies aspects that define the Habeas Corpus, the Court stated the legal sources in which research is a legal basis and notes the Constitution of the Republic of Ecuador, international treaties and conventions , Internal Laws of Ecuador , in comparative law is a synthesis of the most predominant of Habeas Corpus in different countries.